Transforming smallholder farming through remote sensing - Zurita Milla, Raul; By, Rolf A. de (Technical Centre for Agricultural and Rural Cooperation, 2016)
The STARS project explores ways to use remote sensing technology to improve agricultural practices of smallholder farmers in sub-Saharan Africa and South Asia with the aim to advance their livelihoods.